2011
DOI: 10.1128/jb.05132-11
|View full text |Cite
|
Sign up to set email alerts
|

Metabolomics Reveals Phospholipids as Important Nutrient Sources during Salmonella Growth in Bile In Vitro and In Vivo

Abstract: During the colonization of hosts, bacterial pathogens are presented with many challenges that must be overcome for colonization to occur successfully. This requires the bacterial sensing of the surroundings and adaptation to the conditions encountered. One of the major impediments to the pathogen colonization of the mammalian gastrointestinal tract is the antibacterial action of bile. Salmonella enterica serovar Typhimurium has specific mechanisms involved in resistance to bile. Additionally, Salmonella can su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
23
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 32 publications
(24 citation statements)
references
References 23 publications
1
23
0
Order By: Relevance
“…We have previously shown that physiological murine bile supports Salmonella growth at rates comparable to those seen in rich laboratory media (1). In order to begin characterizing the interactions between Salmonella and bile from other organisms, we obtained fresh, physiological bovine bile, adjusted its pH to match that of LB broth (around 7.3), and used it to perform Salmonella growth assays.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…We have previously shown that physiological murine bile supports Salmonella growth at rates comparable to those seen in rich laboratory media (1). In order to begin characterizing the interactions between Salmonella and bile from other organisms, we obtained fresh, physiological bovine bile, adjusted its pH to match that of LB broth (around 7.3), and used it to perform Salmonella growth assays.…”
Section: Resultsmentioning
confidence: 99%
“…We have previously shown that Salmonella can successfully multiply in murine bile, despite the well-known antimicrobial properties of this physiological fluid (1,19). In order to determine the impact of bile on Salmonella gene expression, we performed transcriptome comparisons between Salmonella grown in LB broth and Salmonella grown in physiological murine bile using DNA microarrays.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…We have recently published a metabolomic analysis of the Salmonella infection of the intestinal tract and liver and have shown that Salmonella infection disrupts lipid metabolism in all tissues tested (3). Although the exact compounds affected vary depending on the infected tissue, it is clear that the modulation of host lipid metabolism is a common theme during infection with this pathogen.…”
Section: Discussionmentioning
confidence: 99%